Active Defense : China's Military Strategy Since 1949 - Fravel, M. Taylor (New Jersey Princeton University Press, 2019)
What changes in China's modern military policy reveal about military organizations and strategySince the 1949 Communist Revolution, China has devised nine different military strategies, which the People's Liberation Army (PLA) calls "strategic guidelines." What accounts for these numerous changes? Active Defense offers the first systematic look.
Include Bibliography and Index
Keywords: China -- National security -- Military policy